It is noted that m1=−ab and m2=ac. Hence, m1m2=−a2bc.
According to the diagram, θ1+θ2=90deg. It can also be seen that tanθ1=ab and tanθ2=ac.
As such, taking tan(θ1+θ2)=1−tanθ1tanθ2tanθ1+tanθ2=1−b/a(c/a)b/a+c/a. Since tan(θ1+θ2)=tan90deg=undefined, so from 1−a2bc of the denominator, we get 1=a2bc such that the denominator is zero.
Substituting 1=a2bc back into m1m2=−a2bc, we get m1m2=−1. Hence, it is shown that m1m2=−1.
#Geometry
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
There are no comments in this discussion.